Consumer behavior - Hoyer, Wayne D. (Houghton Mifflin, 1997)
The psychological core: motivation, ability, and opportunity; exposure, attention, and percaption; categorizing and comprehending information; attitude formation and change: high consumer effort; attitude formation and change: low consumer effort; memery and retieval. The process of making decisions: Problem recognition and information search; judgement and decision making: high consumer effort; judgment and decision making: low consumer effort; post-decision processes. The consumer's culture: regional, ethnic, and religious influences on consumer behavior; social calss influences on consumer behavior; age, gender, and household influences on consumer behavior; reference groups and social influence; psychographics: values, personality, and lifestyles. Consumer behavior outcomes. Consumer welfare.